1995
DOI: 10.1002/ajmg.1320550208
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Roberts syndrome

Abstract: Roberts syndrome (RS) is a rare, autosomal recessive condition characterized primarily by growth retardation, developmental delay, and limb anomalies. Some RS patients (RS+), but not others (RS-), have an abnormality of their constitutive heterochromatin (the "RS effect"). RS+ patients also show a cellular hypersensitivity to DNA damaging agents such as mitomycin C (MMC). Lymphoblastoid cell lines from 2 unrelated RS+ patients were fused and hybrid cells examined for correction of the RS effect and MMC hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The RBS-affected individual showed clear evidence of chromosomal instability and increased sensitivity to IR and mitomycin-C. This finding is consistent with a previous report of increased sensitivity to DNA damaging agents, including IR, in fibroblasts derived from RBS patients (7), but differed from another report, which demonstrated that RBS cells were sensitive to several DNA damaging agents,…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The RBS-affected individual showed clear evidence of chromosomal instability and increased sensitivity to IR and mitomycin-C. This finding is consistent with a previous report of increased sensitivity to DNA damaging agents, including IR, in fibroblasts derived from RBS patients (7), but differed from another report, which demonstrated that RBS cells were sensitive to several DNA damaging agents,…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that some RBS patients' cells show hypersensitivity to DNA damaging agents causing DNA dsbs, such as ionizing radiation (IR) and mitomycin C (MMC) (7,8). Another study reported hypersensitivity of RBS fibroblasts to mitomycin C and camptothecin, but not to IR (9).…”
mentioning
confidence: 99%
“…18 The majority (79%) of these children have a characteristic chromosome abnormality, that is, premature centromeric separation (PCS) or "puffing" of the chromosomes caused by repulsion of the heterochromatic regions near the centromeres of chromosomes 1, 9, and 16 with splaying of the short arms of the acrocentric chromosomes and of distal Yp. 33 There is also evidence of abnormal mitosis. 18 Roberts syndrome is thought to be inherited as an autosomal recessive trait.…”
Section: Discussionmentioning
confidence: 99%
“…18 Roberts syndrome is thought to be inherited as an autosomal recessive trait. Urban et al 33 in 1998 postulated that TAR syndrome and Roberts syndrome might be part of the same condition with TAR syndrome being the milder and Roberts the severer variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cell hybridisation experiments suggest that cases of Roberts syndrome with cytogenetic abnormalities and those without those changes do not arise from a single gene mutation [Allingham-Hawkins and Tomkins, 1995]. So far the basic genetic defect in Roberts syndrome is unknown.…”
Section: Historical Contextmentioning
confidence: 99%